Cellular proliferation and activation of NF kappa B are induced by autocrine production of tumor necrosis factor alpha in the human T lymphoma line HuT 78 - O'NEILL, LUKE ANTHONY JOHN (The American Society for Biochemistry and Molecular Biology, 1995)
Tumor necrosis factor (TNF) is a pleiotropic cytokine which has both cytotoxic and proliferative effects. HuT 78, a T-cell line derived from a Sezary lymphoma, is resistant to the cytotoxic effects of TNF, suggesting that TNF may be a growth factor for this cell line. The aim of this study was to determine whether autocrine TNF production could function as a growth factor for HuT 78. Resting HuT 78 and K-4 cells, a protein kinase C-beta-deficient clone of HuT 78, both produced significant amounts of TNF compared with Jurkat cells. Thymidine incorporation by HuT 78 and K-4 cells was inhibited by 90.5 and 73.2%, respectively, with addition of a neutralizing monoclonal antibody to TNF alpha, suggesting that TNF is an autocrine growth factor for these cells. HuT 78 and K-4 cells also expressed high levels of constitutively active NF kappa B, unlike Jurkat cells, which expressed high levels only upon activation with TNF or phorbol 12-myristate 13-acetate. p50 was the major component in the NF kappa B complexes in HuT 78 and K-4 cells. Anti-TNF alpha antibody dramatically decreased levels of NF kappa B in both HuT 78 and K-4 cells. As the TNF gene has an NF kappa B binding motif, an autocrine loop involving TNF induction of NF kappa B is therefore likely in these cells. These findings in a neoplastic T-cell line suggest that therapy directed against TNF could be effective in a subset of T-cell lymphomas.
PUBLISHED
Keywords: Biochemistry